Who Was the Prototype of Aglaya Yepanchina? - N. V. Shevtsov; A. S. Nesterova (Концепт: философия, религия, культура, 2024)
The relevance of turning to the analysis of literary works against the background of biographies of real historical figures is determined primarily by the need to clarify the cultural background, concentratedly presented in artistic refraction. The purpose of this study is to trace new parallels in the lives of the female character of Dostoevsky's novel The Idiot Aglaya Yepanchina and the writer Anna Korvin-Krukovskaya. To achieve this goal, it was necessary: 1) to select the most relevant research material; 2) trace the historical details of the relationship between F. M. Dostoevsky and Anna Korvin-Krukovskaya; 3) analyze the national, social, and political details of the writer’s biography that influenced the image of Aglaya Yepanchina. The work uses a biographical method based on the integrated application of anthropological and axiological approaches. This allows us to trace the life path of Anna Korvin-Krukovskaya on the basis of valuable historical evidence. In addition to the history of communication between A. Korvin-Krukovskaya and F. M. Dostoevsky, the similarity of the story of Aglaya Yepanchina with the further lifepath of A. Korvin-Krukovskaya is also analyzed. In particular, the emigration of A. Korvin-Krukovskaya from Russia, her marriage to V. Jacqular, as well as her participation in political activities are compared with the fate of the heroine of the novel. As a result of the study, similarities in the lives of the writer Anna Korvin-Krukovskaya and Aglaya Yepanchina, the heroine of Dostoevsky's novel The Idiot were confirmed, and previously undescribed biographical analogies of this similarity were highlighted. The following conclusion is substantiated: despite the fact that the presence of autobiographical elements in the works of F. M. Dostoevsky has been repeatedly noted by researchers; a detailed study of the memoirs, correspondence and diaries of the writer and his contemporaries allows us to draw new parallels between the characters of the novel and their prototypes.